A practical look at the why and how of supporting international students: A checklist of teaching tips - Beatty, Shelley; Clark, Kim; Doherty, Sally-Anne (Journal of University Teaching and Learning Practice, 2020)
This paper looks at a pilot of a strategy designed to help academic staff better respond to the inclusive teaching needs of its international students. The strategy was implemented by a School in a Western Australian University and offered academic staff evidence-based information on specific techniques for internationalising curriculum content and delivery. The extent to which international students perceived lecturers had implemented the suggested strategies was subsequently evaluated. While the evaluation found the School had performed adequately in the eyes of its international students across key areas of teaching practice, it also suggested that achieving greater inclusiveness required attention to things beyond classroom processes. These broader aspects included the University’s climate of belongingness and the extent to which the curriculum content took account of international perspectives.